Salicylic acid fights against Fusarium wilt by inhibiting target of rapamycin signaling pathway in Fusarium oxysporum - Linxuan Li; Tingting Zhu; Yun Song; Li Feng; Philip James Kear; Rooallah Saberi Riseh; Mahmoud Sitohy; Raju Datla; Maozhi Ren (Journal of Advanced Research, 2022)
Introduction: Biofungicides with low toxicity and high efficiency are a global priority for sustainable agricultural development. Phytohormone salicylic acid (SA) is an ancient medicine against various diseases in humans and activates the immune system in plants, but little is known of its function as a biofungicide. Objectives: Here, Fusarium oxysporum, the causal agent of devastating Fusarium wilt and immunodepressed patients, was used as a model system to explore whether SA can enter the pathogen cells and suppress key targets of the pathogen. Methods: Oxford Nanopore MinION sequencing and high-throughput chromosome conformation capture (Hi-C) sequencing were used to analyzed the genome of F. oxysporum. In addition, RNA-seq, qRT-PCR, and western blotting were conducted to detect gene and protein expression levels. Results: We isolated and sequenced the genome of F. oxysporum from potato dry rot, and the F. oxysporum included 12 chromosomes and 52.3 Mb genomic length. Pharmacological assays showed that exogenous application of SA can efficiently arrest hyphal growth, spore production, and pathogenicity of F. oxysporum, whereas endogenous salicylate hydroxylases significantly detoxify SA. The synergistic growth inhibition of F. oxysporum was observed when SA was combined with rapamycin. Kinase assays showed that SA inhibits FoTOR complex 1 (FoTORC1) by activating FoSNF1 in vivo. Transgenic potato plants with the interference of FoTOR1 and FoSAH1 genes inhibited the invasive growth of hyphae and significantly prevented the occurrence of Fusarium wilt. Conclusion: This study revealed the underlying mechanisms of SA against F. oxysporum and provided insights into SA in controlling various fungal diseases by targeting the SNF1-TORC1 pathway of pathogens.